Calculus with analytic geometry - Larson, Roland E. 1941-; Hostetler, Robert P.; Edwards, Bruce H.; Heyd, David E. (Boston, MA Houghton Mifflin Company, 1998)
A textbook on analytic geometry and calculus.
Includes index.
Keywords: Calculus; Geometry, Analytic